Antecedents and consequences of residential choice and school transfer. - Falbo, Toni; Glover, Robert W.; Holcombe, W. Lee; Stokes, S. Lynne (Education Policy Analysis Archives, 2005)
This article examines the antecedents and consequences of residential choice and school transfers within one of the eight largest urban school districts in Texas. This study is based on survey data from a representative sample of parents of K-12 students enrolled in this district. In addition to demographic characteristics of the family, the parent decision-making model of Schneider, Teske, & Marschall (2000) was examined to determine if aspects of this model were useful in understanding the school choices made at the beginning of the school year and the parents' motivation to move to another school at the end. The results provide some support for the view that residential choice is related to enhanced achievement and satisfaction; while, within-district transfers were used more by better educated White parents who did not qualify as low income. Parents' motivation to move their children to another school was greater when they perceived the school as less receptive to their involvement and their children as less successful in school.